Expand (4√3 − 3√5)^2
Answers
Answered by
7
this is the solution for your question
Attachments:
![](https://hi-static.z-dn.net/files/d00/d70006cba0664055ce19638eeff2d99e.jpg)
Elakkeyen001:
THX
Answered by
7
Thanks for the question!
![(4 \sqrt{3} -3 \sqrt{5} ) ^{2} \: \\ \\ = (4 \sqrt{3} ) ^{2} + (3 \sqrt{5}) ^2 - 2(4 \sqrt{3})(3 \sqrt{5} )<br /><br />\\ \\ = (16 \times 3 ) + ( 9 \times 5 ) + 24 \sqrt{15} \\ \\ = 48 + 45 -24 \sqrt{15} \\ \\ = 93 - 24 \sqrt{15} <br /><br /> (4 \sqrt{3} -3 \sqrt{5} ) ^{2} \: \\ \\ = (4 \sqrt{3} ) ^{2} + (3 \sqrt{5}) ^2 - 2(4 \sqrt{3})(3 \sqrt{5} )<br /><br />\\ \\ = (16 \times 3 ) + ( 9 \times 5 ) + 24 \sqrt{15} \\ \\ = 48 + 45 -24 \sqrt{15} \\ \\ = 93 - 24 \sqrt{15} <br /><br />](https://tex.z-dn.net/?f=%284+%5Csqrt%7B3%7D+-3+%5Csqrt%7B5%7D+%29+%5E%7B2%7D+%5C%3A+%5C%5C+%5C%5C+%3D+%284+%5Csqrt%7B3%7D+%29+%5E%7B2%7D+%2B+%283+%5Csqrt%7B5%7D%29+%5E2+-+2%284+%5Csqrt%7B3%7D%29%283+%5Csqrt%7B5%7D+%29%3Cbr+%2F%3E%3Cbr+%2F%3E%5C%5C+%5C%5C+%3D+%2816+%5Ctimes+3+%29+%2B+%28+9+%5Ctimes+5+%29+%2B+24+%5Csqrt%7B15%7D+%5C%5C+%5C%5C+%3D+48+%2B+45+-24+%5Csqrt%7B15%7D+%5C%5C+%5C%5C+%3D+93+-+24+%5Csqrt%7B15%7D+%3Cbr+%2F%3E%3Cbr+%2F%3E)
![\boxed{ Formulae \: used \: : ( a - b) ^2 = a^2 + b^2 + 2ab } \boxed{ Formulae \: used \: : ( a - b) ^2 = a^2 + b^2 + 2ab }](https://tex.z-dn.net/?f=+%5Cboxed%7B+Formulae+%5C%3A+used+%5C%3A+%3A+%28+a+-+b%29+%5E2+%3D+a%5E2+%2B+b%5E2+%2B+2ab+%7D+)
(or)
(4√3 − 3√5)^2
= 4√3 - 3√5 * 4√3 - 3√5
= 4√3 ( 4√3 - 3√5 ) - 3√5( 4√3 - 3√5)
= 16(3) - 12√15 - 12√15 + 9(5)
= 48 + 45 - 24√15
= 93 - 24√15
Hope helped!
(or)
(4√3 − 3√5)^2
= 4√3 - 3√5 * 4√3 - 3√5
= 4√3 ( 4√3 - 3√5 ) - 3√5( 4√3 - 3√5)
= 16(3) - 12√15 - 12√15 + 9(5)
= 48 + 45 - 24√15
= 93 - 24√15
Hope helped!
Similar questions